Piezoelectric Response of Porous Nanotubes Derived from Hexagonal Boron Nitride under Strain Influence - Fabris, Guilherme S. L. [UNESP]; Marana, Naiara L. [UNESP]; Longo, Elson; Sambrano, Julio R. [UNESP] (Amer Chemical Soc, 2018)
A computational study via periodic density functional theory of porous nanotubes derived from single-layer surfaces of porous hexagonal boron nitride nanotubes (PBNNTs) and inorganic graphenylene-like boron nitride nanotubes (IGP-BNNTs) has been carried out with the main focus in its piezoelectric behavior. The simulations showed that the strain provides a meaningful improve in the piezoelectric response on the zigzag porous boron nitride nanotubes. Additionally, its stability, possible formation, elastic, and electronic properties were analyzed, and for comparison purpose, the porous graphene and graphenylene nanotubes were studied. From the elastic properties study, it was found that IGP-BNNTs exhibited a higher rigidity because of the influence of the superficial porous area, as compared to PBNNTs. The present study provides evidence that the strain is a way to maximize the piezoelectric response and make this material a good candidate for electromechanical devices.